1993
DOI: 10.1016/0304-3959(93)90167-n
|View full text |Cite
|
Sign up to set email alerts
|

Polymedication and medication compliance in patients with chronic non-malignant pain

Abstract: Most reports of polymedication among patients with chronic non-malignant pain have relied only on the patient's statements which have been proven to be unreliable regarding actual drug consumption. This study investigates the incidence of polymedication and medication compliance in these patients by applying objective methods. One-hundred-nine consecutive patients predominantly with facial, neuropathic or back pain were interviewed about present medication at first admission to the pain clinic. Reports were ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
81
0
4

Year Published

1996
1996
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(86 citation statements)
references
References 26 publications
1
81
0
4
Order By: Relevance
“…Regular use of high amounts of drugs is often not taken into consideration when treatment is planned. Moreover, the consumption verified by blood tests is often higher than the reported medication (19). The present study identified a subgroup of patients on polymedication for shoulder pain.…”
Section: Discussionmentioning
confidence: 89%
“…Regular use of high amounts of drugs is often not taken into consideration when treatment is planned. Moreover, the consumption verified by blood tests is often higher than the reported medication (19). The present study identified a subgroup of patients on polymedication for shoulder pain.…”
Section: Discussionmentioning
confidence: 89%
“…Berndt, Maier e Schütz 13 (1993) também não encontraram relação entre o local e a intensidade da dor e a adesão ao tratamento. Acreditava-se que pacientes com dores generalizadas e maior tempo de dor teriam maior aderência à terapia, o que não foi observado.…”
Section: Resultados Adesão Ao Tratamentounclassified
“…Supunha-se que a adesão seria mais elevada no início e diminuiria com o tempo, o que não ocorreu. Os índices de não adesão e de acerto de ingestão medicamentosa observados assemelharam-se aos encontrados em outros trabalhos (8)(9)(10) , que também descrevem valores entre 30% e 70% de não adesão ou adesão parcial. Tais dados são preocupantes e indicam a necessidade de intervenções que melhorem a adesão.…”
Section: Discussionunclassified